Replacement of corn silage with spineless cactus in sheep diet: carcass and meat sensory characteristics - Ribeiro, Julimar do Sacramento; Moreno, Greicy Mitzi Bezerra; Vieira, Marianna Suellen Bispo; Silva, Maria Josilaine Matos dos Santos; Lima, Carolyny Batista; Mariz, Tobyas Maia de Albuquerque; Santos, Luana Lira; Lima Júnior, Dorgival Morais de (Acta Scientiarum. Animal Sciences, 2020)
This study evaluated the effect of replacing corn silage with spineless cactus, in combination with Tifton 85 hay or sugarcane bagasse, on the carcass measurements and sensory properties of the meat of lambs finished in feedlot. Twenty-one, intact, Santa Inês males, with an initial body weight of 22.86 ± 2.87 kg and an average age of 150 days, were individually confined for 74 days and fed at will three treatments diets: Corn silage (CS); Spineless cactus + Tifton 85 hay (CT) and Spineless cactus + sugarcane bagasse (CB). Lambs fed CT had a wider croup (p < 0.05) compared to animals fed CS. The replacement of corn silage with CT or CB did not influence (p > 0.05) the body length, withers height or chest circumference of the lambs. Values of carcass length and compactness index were similar (p > 0.05) between treatments. There was a high and positive correlation (p < 0.05) between chest width (0.82) and chest circumference (0.81) of animals with cold carcass weight. The odor and taste of sheep meat fed CT or CB was more accepted when compared to the meat of animals fed corn silage. The replacement of corn silage with spineless cactus in combination with Tifton 85 hay or sugarcane bagasse improves the sensory quality of sheep meat, but does not interfere with carcass measurements.